Keterkaitan Penelitian Pendidikan Dengan Pendidikan Islam Di Indonesia - Indirwan; Zulkifli; Yuliana; Sari, Nurfauzia (LP2M Universitas Islam Ahmad Dahlan, 2023)
This study aims to determine the linkages between educational research and Islamic education in Indonesia. The method used in this research is (library research), also known as the data collection method, by understanding and studying theories from various readers related to this research. The data collection technique used by the author is to find and select theories from various reference sources such as books, journals, and existing research. The results of the author's analysis, namely the link between educational research and social research are focused on the process of social interaction between educators and students. academic learning activities. Educational research is a method used to solve problems that arise in the field of education. In addition, there are issues that include poverty and unemployment, and other factors such as learning, health, and development opportunities that can affect human development. As for how to improve teacher behavior in teaching, namely by understanding teacher needs and motivation, understanding teacher competence, understanding the teacher's role in teaching, teacher and student interaction, the main target of educational success